Real-world Safety of Bevacizumab with First-line Combination Chemotherapy in Patients with Metastatic Colorectal Cancer: Population-based Retrospective Cohort Studies in Three Canadian Provinces. Issue 1 (January 2022) - Beca, J.M.; Dai, W.F.; Pataky, R.E.; Tran, D.; Dvorani, E.; Isaranuwatchai, W.; Peacock, S.; Alvi, R.; Cheung, W.Y.; Earle, C.C.; Gavura, S.; Chan, K.K.W.
Abstract: Aims: To examine the real-world safety of adding bevacizumab to first-line irinotecan-based chemotherapy for patients with metastatic colorectal cancer (mCRC). Materials and methods: Patients diagnosed with CRC in three Canadian provinces (Ontario, Saskatchewan and British Columbia) who received publicly funded bevacizumab and/or irinotecan from 2000 to 2016 were identified from cancer registries. Propensity score 1:1 matching (PSM) and inverse probability of treatment weighting (IPTW) were performed to contemporaneous and historical controls, adjusting for baseline demographic and clinical characteristics. Safety end points evaluated during first-line treatment plus 30 days included mortality within 30 days and all-cause-, chemotherapy- and bevacizumab-related hospitalisations. Chemotherapy- and bevacizumab-related visits were defined as hospitalisations for specific conditions commonly associated with chemotherapy (e.g. infections) or bevacizumab (e.g. arteriovenous thromboembolism) using most responsible diagnosis codes. In PSM and IPTW-weighted cohorts, we assessed event frequencies using odds ratios from logistic regressions and event rate ratios using negative binomial regression models. The results from each province and comparison were pooled using random-effects meta-analysis. Results: We identified 16 250 mCRC patients who received first-line irinotecan-based treatment. In PSM cohorts, bevacizumab was associated with fewer deaths within 30 days of treatment compared with contemporaneous (pooled odds ratio = 0.62; 95% confidence interval 0.50–0.75) and historical controls (pooled odds ratio = 0.73; 95% confidence interval 0.58–0.93). Hospitalisations were more frequent among patients treated with bevacizumab compared with historical controls but similar to contemporaneous controls. As patients receiving bevacizumab were exposed to a longer average treatment duration, across their full treatment duration, patients receiving bevacizumab had significantly lower rates of hospitalisations (contemporaneous pooled rate ratio = 0.56; 95% confidence interval 0.47–0.67; historical pooled rate ratio = 0.73; 95% confidence interval 0.56–0.95). Similar trends were observed for chemotherapy- and bevacizumab-related hospitalisations and in IPTW-weighted cohorts. Discussion: We did not observe any increase in rates of hospitalisation or death within 30 days of treatment among mCRC patients treated with bevacizumab plus chemotherapy versus chemotherapy alone; these findings should be interpreted with caution due to the risk of residual confounding. Highlights: Bevacizumab with chemotherapy to treat metastatic colorectal cancer increased hospital visits during treatment compared with chemotherapy alone. Patients receiving bevacizumab experienced lower rate of hospitalisation over longer treatment duration than chemotherapy alone. No observed increase in deaths within 30 days of treatment suggests bevacizumab toxicity to be manageable in the real world. Comparative real-world safety evaluation with population-based administrative data enables valuable ongoing pharmacovigilance.